PTU-114 Safety of accelerated infliximab infusion in inflammatory bowel disease in a district general hospital. (8th June 2018) - Luk, Jeffrey; Avery, Pearl; Wilson, Rosetta; Lock, Annie; Webb, Elizabeth; Jupp, James; Castro-Silva, Angel; Bridger, Stephen; Shutt, James
Abstract : Introduction: Our district general hospital serves a population of around 3 30 000 with 1325 active Inflammatory Bowel Disease (IBD) patients. A small percentage of these patients receive infliximab infusions for disease control. The British National Formulary states that infliximab infusion should follow the following infusion schedule: 5 infusions over 2 hours (hr) with 2 hour of post-infusion monitoring, with subsequent infusions delivered over 1 hour with 1 hour of monitoring. With published data supporting an accelerated infusion regimen, after 10 incident-free infusions we administer infliximab over 30 min (min) with 30 min observation. Recently a patient established on infliximab from another centre challenged our practice seeking assurance of its safety. Our primary endpoint was to assess the safety of accelerated infusion protocol, with secondary assessment of efficiency. Methods: Using the local patient management system which supports the IBD registry data tool, we retrospectively identified all patients with IBD who underwent infliximab infusions in 2017. All followed our standard protocol of five infusions over 2 hour with 2 hour of monitoring, the next five over 1 hour with 1 hour monitoring and subsequent infusions over 30 min with 30 min of post-infusion monitoring. Results: Over the 12 months, 202 infusions were given to 39 patients with IBD (30 Crohn's, 1 Ulcerative Colitis, 1 unclassified). Fifty nine induction infusions were administered over 2 hour and 10 over 1 hour, with 133 infusions over 30 min. Only 1 infusion reaction was reported in the induction phase (1.4%). The reaction occurred within 10 min of commencement of the infusion and was anaphylactoid in nature. The patient was taken off infliximab and is now on ustekinumab. The remaining 201 infusions were reaction free, including all of the accelerated infusions. The accelerated infusions saved a total of 1 hour per patient visit to the infusion unit. As well as the benefit to patients, this has allowed the Trust to free up 13 days of infusion time per annum on our current case load. Conclusions: Accelerated infliximab infusions over 30 min were safe and the time saved enhances our unit's capacity, consistent with the wider evidence available in the literature. If other units across the country also share the same safety profile of accelerated infliximab infusions, then the guidance can be updated, resulting in an overall increase in the efficiency of infusion units.